2017
DOI: 10.1371/journal.pone.0177621
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of members of the ethylene signaling–related gene families in response to dehydration stresses in cassava

Abstract: Drought is the one of the most important environment stresses that restricts crop yield worldwide. Cassava (Manihot esculenta Crantz) is an important food and energy crop that has many desirable traits such as drought, heat and low nutrients tolerance. However, the mechanisms underlying drought tolerance in cassava are unclear. Ethylene signaling pathway, from the upstream receptors to the downstream transcription factors, plays important roles in environmental stress responses during plant growth and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…The ABF family of bZIP transcription factors functions in ABA signaling pathways and plays an important role in plant responses to stresses 18,21 . Here we found that in various cassava organs, MeABFs exhibited differential expression patterns after drought, osmotic, and salt stress treatments(Figs 2–5), which was consistent with trends we observed in cassava in our previous study that identified genes involved in ethylene signaling in response to dehydration stresses 8 . Our results of this study showed that drought stress in cassava leaves and roots, osmotic stress in cassava tuberous roots, and salt stress in cassava stems induced expression of the highest number of MeABFs in terms of significantly elevated expression (Supplementary Tables S5, S8, S11 and S14).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The ABF family of bZIP transcription factors functions in ABA signaling pathways and plays an important role in plant responses to stresses 18,21 . Here we found that in various cassava organs, MeABFs exhibited differential expression patterns after drought, osmotic, and salt stress treatments(Figs 2–5), which was consistent with trends we observed in cassava in our previous study that identified genes involved in ethylene signaling in response to dehydration stresses 8 . Our results of this study showed that drought stress in cassava leaves and roots, osmotic stress in cassava tuberous roots, and salt stress in cassava stems induced expression of the highest number of MeABFs in terms of significantly elevated expression (Supplementary Tables S5, S8, S11 and S14).…”
Section: Discussionsupporting
confidence: 91%
“…Since the plants lived for 18 days after drought treatment, we collected materials at 0 d, 3 d, 6 d, 9 d, 12 d, 15 d and 18 d after drought treatment. For osmotic or salt stress treatments, samples were collected at 0, 1, 2, 4, 8, 12, and 24 h after treatment with 400 mM NaCl or 30% PEG-6000 8 . For the control, cassava plants were watered on intervals of every three days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations